The full-system approach for elastohydrodynamic lubrication - Fillot, Nicolas (2017)
A ball is in contact with a plane, and a lubricant separates the two surfaces to decrease friction during their relative motion. To avoid wear, the lubricant film thickness should be higher than the surface roughness. The goal of this paper is to show how it is possible to solve efficiently the problem of elastohydrodynamics lubrication with Comsol Multiphysics, using a PDE on boundary to implement the Reynolds equation.